The Bulgarian Commission for Protection against Discrimination as a National Jurisdiction within the meaning of Article 267 of the TFEU - History and Prospects - Yocheva, Katerina (Yearbook of the Law Department, 2023)
The subject of analysis in the study are the conditions that a national authority should meet in order to meet the requirements for "national jurisdiction", which can make reference to the Court of Justice of the EU (CJEU) within the framework of a preliminary ruling procedure under Article 267 TFEU. In particular, under consideration is the possibility of the Bulgarian Commission for Protection against Discrimination to receive recognition as a national jurisdiction upon fulfilment of the established by the CJEU conditions. For this purpose, the practice of the Commission for Protection against Discrimination itself in this regard is examined, as well as the opinion of the CJEU on the matter. The prospects for changing the current situation are also discussed in view of the amendments to the Statute and the Rules of Procedure of the EU jurisdictions, under which competences in the framework of the preliminary ruling procedure are partially granted to the General Court, as of 1 October 2024.